KORELASI ASPEK KOGNITIF TERHADAP SIKAP DALAM PEMERIKSAAN PAP SMEAR PADA WANITA USIA SUBUR - Noviasari, Damai; Noorma, Nilam; Saptaningrum, Epi; Sariyani, Made Dewi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Cervical cancer is the second leading cause of cancer in women. Cervical cancer screening in Indonesia is still relatively low, even though this disease is one of the leading causes of death in women. The results of an initial survey conducted in Getas Village RT 05, 06, 07 to 10 women of childbearing age. Information was obtained that 80% of WUS did not know about cervical cancer, 100% of WUS had never done cervical cancer screening, 20% were afraid of pap smear examination, 30% of WUS had sufficient education, 50% had low education, 20% of WUS did not go to school. The purpose of this study was to determine the correlation of cognitive aspects of attitudes towards pap smear examination in women of childbearing age. The research design used in this study was cross sectional. The research was conducted in August 2023 in Getas Village. The population in the study were all married women of childbearing age totaling 150 people. The sample amounted to 109 people. The sampling technique used probability sampling with Simple Random Sampling technique. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between knowledge about cervical cancer and attitudes towards papsmear examination with a p value of 0.000. It is recommended for Puskesmas to provide explanations and health information more often about cervical cancer as a promotive effort and for the community, especially women of childbearing age, it is recommended to seek additional information about cervical cancer and other early detection.Keywords: Income, History of Infectious Disease, Stunting.